THE IMPACT OF BEAUTY CONSULTING ON THE DEVELOPMENT OF WOMEN’S ENTREPRENEURSHIP: A CASE STUDY OF THE LICENSE SOLUTION CONSULTING PROJECT - Блажко, Катерина (SWorldJournal, 2026)
Women’s entrepreneurship is a key driver of economic growth and social integration, particularly within the service sector, where women often face specific institutional and structural barriers. The beauty industry, as one of the most accessible fields fo